2012
DOI: 10.1152/physrev.00047.2011
|View full text |Cite
|
Sign up to set email alerts
|

S-adenosylmethionine in Liver Health, Injury, and Cancer

Abstract: S-adenosylmethionine (AdoMet, also known as SAM and SAMe) is the principal biological methyl donor synthesized in all mammalian cells but most abundantly in the liver. Biosynthesis of AdoMet requires the enzyme methionine adenosyltransferase (MAT). In mammals, two genes, MAT1A that is largely expressed by normal liver and MAT2A that is expressed by all extrahepatic tissues, encode MAT. Patients with chronic liver disease have reduced MAT activity and AdoMet levels. Mice lacking Mat1a have reduced hepatic AdoMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
618
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 450 publications
(637 citation statements)
references
References 277 publications
(497 reference statements)
7
618
1
11
Order By: Relevance
“…SAM is an important metabolite as it serves as a major donor of methyl groups in numerous reactions involving methylation of DNA, RNA, proteins and metabolites [4][5][6] . Thus, in addition to its essential role in polyamine synthesis, AdoMetDC may also influence methylation reactions by affecting SAM availability.…”
Section: Adometdc Catalyses the Decarboxylation Of S-adenosylmethionimentioning
confidence: 99%
“…SAM is an important metabolite as it serves as a major donor of methyl groups in numerous reactions involving methylation of DNA, RNA, proteins and metabolites [4][5][6] . Thus, in addition to its essential role in polyamine synthesis, AdoMetDC may also influence methylation reactions by affecting SAM availability.…”
Section: Adometdc Catalyses the Decarboxylation Of S-adenosylmethionimentioning
confidence: 99%
“…Thus, the interesting possibility exists that the interaction of these enzymes with ETF is more sensitive to ETF␤ methylation status than what is the case for the enzymes tested here. Recent studies have indicated that cellular SAM levels are subject to tight regulation, and the one-carbon units generated by DMGDH and SARDH can actually be used for replenishment of the cellular SAM pool (33). Thus, the interesting, though speculative, possibility exists that METTL20 acts as SAM sensor, which in a SAM-dependent manner regulates the flow of electrons from DMGDH and/or SARDH to ETF, thereby regulating the level of one-carbon units available for SAM synthesis.…”
Section: Identification Of Human Mettl20 As Mitochondrial Kmtmentioning
confidence: 99%
“…methionine adenosyltransferase | cell growth | liver cancer | X-ray crystallography | methylation T ransmethylation, the transfer of a methyl group from one molecule to another, is a fundamental chemical reaction that plays a central role in important biological processes such as gene expression, cell growth, and apoptosis (1). The highly conserved methionine adenosyltransferase (MAT) enzymes synthesize the main source of methyl groups in all living organisms in the form of S-adenosylmethionine (SAMe) (2).…”
mentioning
confidence: 99%
“…For example, mutations involving the MAT1A gene have links with hepatic MAT deficiency which leads to hypermethioninemia (6,7). Expression of MATα2 confers a growth advantage in cells and is important for differentiation and apoptosis (1) in diseases such as human hepatocellular carcinoma (5), colon cancer (8), and leukemia (9).…”
mentioning
confidence: 99%